2017
DOI: 10.3346/jkms.2017.32.3.514
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of QEEG Findings between Adolescents with Attention Deficit Hyperactivity Disorder (ADHD) without Comorbidity and ADHD Comorbid with Internet Gaming Disorder

Abstract: Internet gaming disorder (IGD) is often comorbid with attention deficit hyperactivity disorder (ADHD). In this study, we compared the neurobiological differences between ADHD comorbid with IGD (ADHD+IGD group) and ADHD without comorbidity (ADHD-only group) by analyzing quantitative electroencephalogram (QEEG) findings. We recruited 16 male ADHD+IGD, 15 male ADHD-only adolescent patients, and 15 male healthy controls (HC group). Participants were assessed using Young's Internet Addiction Scale and ADHD Rating S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 39 publications
0
43
1
Order By: Relevance
“…Overall, VBM research has been helpful in demonstrating potential structural brain changes of IGD individuals. Many of the brain regions found to be altered in IGD individuals have been previously linked to functions contributing to the development of addictive or compulsive behaviors ( 48 ). For example, decreased OFC thickness has been identified in individuals with substance-use disorders and behavioral addictions, further implying the development of IGD may involve brain regions similar to those involved in these conditions ( 49 , 50 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, VBM research has been helpful in demonstrating potential structural brain changes of IGD individuals. Many of the brain regions found to be altered in IGD individuals have been previously linked to functions contributing to the development of addictive or compulsive behaviors ( 48 ). For example, decreased OFC thickness has been identified in individuals with substance-use disorders and behavioral addictions, further implying the development of IGD may involve brain regions similar to those involved in these conditions ( 49 , 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Park et al ( 48 ), the authors noted that IGD is often comorbid with attention deficit hyperactivity disorder (ADHD). Using quantitative electroencephalogram (QEEG) they compared three adolescent groups: males with ADHD and IGD ( n = 16), male ADHD-only ( n = 15), and a control group ( n = 15).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that altered neural networks for executive control in ADHD would be a predisposition for developing IGD. Furthermore, a study that used qualitative EGG to compare adolescents with IGD with or without ADHD found that Adolescents who show greater vulnerability to ADHD seem to continuously play Internet games to enhance attentional ability ( 92 ). Second, repetitive activation of brain reward and working memory systems during continuous gaming may result in an increase in neuronal connectivity within the parieto-occipital and temporal regions for the comorbid ADHD and IGD participants ( 92 ).…”
Section: Brain Imaging Studies On Dopamine 5-ht and Comorbid Psychiamentioning
confidence: 99%
“…Furthermore, a study that used qualitative EGG to compare adolescents with IGD with or without ADHD found that Adolescents who show greater vulnerability to ADHD seem to continuously play Internet games to enhance attentional ability ( 92 ). Second, repetitive activation of brain reward and working memory systems during continuous gaming may result in an increase in neuronal connectivity within the parieto-occipital and temporal regions for the comorbid ADHD and IGD participants ( 92 ). Finally, a study that investigated the comorbidity of IGD with depression found that IGD participants with comorbid major depressive disorder (MDD) who performed on the Wisconsin card sorting task showed failure to suppress activity in the hippocampus during an attention demanding task, possibly as a consequence of depression ( 93 ).…”
Section: Brain Imaging Studies On Dopamine 5-ht and Comorbid Psychiamentioning
confidence: 99%
“…Recently, there have been attempts to determine characteristic features of IGD using spectral analysis of QEEG (789). Participants with IGD had lower absolute power in the beta band and higher absolute power in the gamma band compared with healthy controls (78).…”
Section: Introductionmentioning
confidence: 99%